Importance of serrated polyps in colorectal carcinogenesis. (19th October 2012) - Liang, Jennifer J.; Bissett, Ian; Kalady, Matthew; Bennet, Ana; Church, James M.
Abstract: Colorectal cancer is an invasive neoplasm of the glandular epithelium of the colon and rectum that begins in a precursor lesion and expands to replace its lesion of origin. The majority of colorectal cancers arise from an adenoma, and the 'adenoma to carcinoma' pathway has been acknowledged for decades. More recently, another precursor lesion has been recognized: the serrated polyp. Serrated polyps are characterized by a sawtooth appearance of the crypt epithelium resulting from failure of apoptosis and a build‐up of aging colonocytes. Although initially felt to be innocent of involvement in colorectal carcinogenesis, some types of serrated polyp are being increasingly recognized as precursor lesions, prone to develop into cancer, and likely to be a cause of 'missed' or interval cancers after colonoscopic screening. It is essential that gastrointestinal specialists appreciate the clinical significance of these lesions and what that means for colorectal cancer screening, and prevention. The purpose of this review is to highlight the importance serrated lesions of the colon and rectum, and to summarize current opinion on their natural history, diagnosis, surveillance and treatment.